Corporate Charter Function Analysis In Indonesia to Control Financial Conglomeration Institution (Based on Financial Services Authority Regulation Number 45/POJK.03/2020 regarding Financial Conglomerates) - Andar Sudiar Sukma; Mohamad Fajri Mekka Putra (Budapest International Research and Critics University, 2022)
The Financial Services Authority has issued Financial Services Authority Regulation Number 45 / POJK.03 / 2020 concerning Financial Conglomerates. In the POJK, each financial conglomerate is required to make a Corporate Charter, which is an agreement between the Main Entity of the LJK and the Member Entity of the LJK in the corporation. There is a minimum of substance stipulated in the Corporate Charter so that OJK can conduct a supervisory function for the Financial Conglomeration. The main issues discussed were whether the corporate charter could be effectively used as a supervisory tool for OJK and whether the Corporate Charter would benefit the Main Entity if it was implemented. This paper concludes that the Corporate Charter will not be fully effective if it is used as a monitoring tool because the substances stipulated in the Corporate Charter are not yet perfect and need to expand the scope of duties and responsibilities between the main entity and member LJK entities. This paper also concludes that the Corporate Charter itself for the Main Entity can also provide benefits, namely serving as a tool to convey the main entity's policies to LJK member entities so that between the main entity and the parent entity there is a moving harmony.